Response time under monetary incentives: the ultimatum game - Pablo Bra\~nas-Garza; Ana León-Mejía; Luis M. Miller (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
This paper studies the response times of experimental subjects playing the Ultimatum game in a laboratory setting using monetary incentives. We find that proposals are not significantly correlated with response time, whereas responders behavior is positively and significantly correlated. Hence, consistent with Rubisntein (forthcoming) we find that response times may capture relevant cognitive processes. However, the use of monetary incentives causes a reversal of his findings. These results have implications for the information about cognitive mechanisms that can be obtained from response times.
Keywords: C72; C91; 330; Monetary incentives; Ultimatum game; response time; Nichtkooperatives Spiel; Verhandlungstheorie; Zeit; Ökonomischer Anreiz; Test